Non-Native & Native English Teachers - Tosuncuoglu, İrfan (Journal of History Culture and Art Research, 2017)
In many countries the primary (mother tongue) language is not English but there is a great demand for English language teachers all over the world. The demand in this field is try to be filled largely by non-native English speaking teachers who have learned English in the country or abroad, or from another non native English peaking teachers. In some countries, particularly those where English speaking is a a sign of status, the students prefer to learn English from a native English speaker. The perception is that a non-native English speaking teacher is a less authentic teacher than a native English speaker and their instruction is not satifactory in some ways. This paper will try to examine the literature to explore whether there is a difference in instructional effectiveness between NNESTs and native English teachers.